(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted research of legal category «sources of law» on example of civil procedure law. Basic scientific approaches are analysed on this question. The author formulated a concept, personal touches and functions of sources of civil procedure law. Keywords: sources of law, civil procedure law.